Perceived Corporate Politics and Political Behavior: Cause or Effect for Each Other - Bhattarai, Ganesh (Pravaha, 2020)
In the literature of corporate politics, directionality (cause or effect) of the relationship between perceived corporate politics and political behavior is unsettled. This study was carried out to measure the association between employee's perceived corporate politics and their political behavior as a response to such context. Positivist research philosophy, deductive reasoning approach of research, and inferential statistic were adopted to infer the conclusion. Perceptual cross-sectional data were taken from the employees working in the Nepalese Banking industry. Structural Equation Modeling, using Analysis of Momentum Structure, was adopted to calculate the results. Data analysis of 725 respondents revealed that employees' perceived corporate politics positively affected their political behavior regarding self-promotion and ingratiation. Moreover, this study measured that employees' self-promoting behavior causes to predict their ingratiating behavior at the workplace. Practical implications, theoretical implications, and direction for further study are recommended.